Research Progress on Emerging Viral Pathogens of Small Ruminants in China during the Last Decade - Li Mao; Wenliang Li; Fei Hao; Leilei Yang; Jizong Li; Min Sun; Wenwen Zhang; Maojun Liu; Xuenong Luo; Zilong Cheng (Viruses, 2022)
China is the country with the largest number of domestic small ruminants in the world. Recently, the intensive and large-scale sheep/goat raising industry has developed rapidly, especially in nonpastoral regions. Frequent trading, allocation, and transportation result in the introduction and prevalence of new pathogens. Several new viral pathogens (peste des petits ruminants virus, caprine parainfluenza virus type 3, border disease virus, enzootic nasal tumor virus, caprine herpesvirus 1, enterovirus) have been circulating and identified in China, which has attracted extensive attention from both farmers and researchers. During the last decade, studies examining the etiology, epidemiology, pathogenesis, diagnostic methods, and vaccines for these emerging viruses have been conducted. In this review, we focus on the latest findings and research progress related to these newly identified viral pathogens in China, discuss the current situation and problems, and propose research directions and prevention strategies for different diseases in the future. Our aim is to provide comprehensive and valuable information for the prevention and control of these emerging viruses and highlight the importance of surveillance of emerging or re-emerging viruses.